If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + 5g = 8g Combine like terms: 3g + 5g = 8g 8g = 8g Add '-8g' to each side of the equation. 8g + -8g = 8g + -8g Combine like terms: 8g + -8g = 0 0 = 8g + -8g Combine like terms: 8g + -8g = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| (3x-1)(3x+3)=3x(3x+1) | | -11+48+11-48+12= | | 3x-7=8x-21 | | 86+65-14-65+14= | | 39-14-39+14-23= | | 67+12+16-67-26= | | 0-10y=-80 | | 8x-0=-80 | | M+0.9+0.5m=-2.1 | | x^3-6x-20=0 | | 2x^2+14x-3=0 | | (2x-6)+4=4x-22 | | 2x-6+4=4x-22 | | 2x-3+4=4x-22 | | 14-8x=199-43x | | 11-8x=73-22x | | 14x+(x-7)-(3x+11)=40 | | 5x-(2x+6)=24 | | 2x-6+4=22+4x | | 2x+155=12x-5 | | 76-3x=15x+20 | | 2x-3+4=22+4x | | x-17=29 | | 6x-3=13x-35 | | 6x+0=18 | | 6(0)+3y=18 | | x^2-y^2=(x-2y)(x^2+y^2) | | 2x=3x^2-4xy+y^2 | | x^2+3x+13=0 | | (x-2)(x+3)-3=0 | | x^3-x=32 | | 2x+9=-8-7x |